STRATEGIES FOR MANAGING CONFLICT IN AN ORGANISATION - SHONHIWA, DOCTOR CAXTON (IJRDO- Journal of Educational Research, 2017)
This present paper proffers some suggestions on how organisations can manage conflict so that itdoes not disrupt their operations. Conflict, if not dealt with properly, can cause serious damageto an organisation. A huge amount of energy can go into internal conflicts, petty disputes andpersonal battles. Good managers spot conflicts as or even before they arise and deal with themas effectively and efficiently as if they were dealing with fires in the building. Organisations areliving systems consisting of interacting units performing a task in a mutually dependant mannerwithin a structure of scarce resources. It seems common place to suggest that conflicts would bepresent in such a setting. The parties in an organisation may have a conflict about thedistribution of resources, or they may have a more fundamental conflict about the very structureof their organisation and the basic nature of their interaction. Once the parties are in a situationof goal incompatibility, their conflict develops in a dynamic fashion, initiating valuable andmuch-needed constructive changes or leading to escalating strategies and destructiveconsequences. Managers must accept the need to influence the developmental dynamics of aconflict so that the parties’ attitudes and actions will lead to better coordination and a moreappropriate interdependence. They must not seek to stifle or eliminate organisational conflict;for that is hardly a realistic goal. The challenge managers face is to utilise such conflictmanagement techniques that would ensure that as a conflict passes from a latent to a manifestphase, it proceeds towards its potential and realizes its constructive values.